PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR FISIKA PESERTA DIDIK PADA POKOK BAHASAN SUHU DAN KALOR - Akbar Purbowo; Bonefasius Yanwar Boy; Indah Slamet Budiarti (Papua Journal of Physics Education, 2020)
The purpose of this research is to determine the improvement of learning outcomes and the difference of students’ science process skill between the experimental class taught by Student Teams Achievement Division (STAD) as learning model with the control class taught by conventional learning model on the subject of temperature and heat. This research used quantitative method with quasi experimental design. The sample in this research is class X IPA 1 and X IPA 2 of SMA Pembangunan V Yapis Waena. Samples were taken from purposive sampling technique. Improvement on learning outcomes can be seen from the n-gain value of all concepts taught by using STAD as cooperative learning model. The n-gain score was 0.61 so that the learning outcomes were classified as moderate. There are significant differences in science process skills between learners who were thaught using STAD as cooperative learning model and conventional learning model for the whole concept of temperature and heat. The findings indicated signification value of 0,05 which is 0,000. The findings were found in the whole concept of temperature and heat concept, concept of expansion and heat transfer concept.Keywords: Model of cooperative learning, type Student Teams Achievement Division (STAD), science process skills, learning outcomes, temperature and heat.